Implementation of Public Relations Management in Increasing Community Participation - Andi Ahmad Wahib; St. Syamsudduha; Yuspiani Yuspiani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to determine the implementation of public relations management in increasing community participation at MI Assalam Ancu. This study uses a qualitative research type with a participatory, thematic and integrative research approach. The data sources for this study are the principal of the madrasah, the madrasah committee, public relations employees/staff, parents of students and local community leaders. Furthermore, the data collection methods used are observation, interviews, documentation, and reference searches. Then, data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of public relations management at Madrasah Ibtidaiyah Assalam, Kajuara District, Bone Regency has been carried out well, with the application of management functions, namely: planning, organizing, directing, monitoring, and evaluating in every public relations activity. Community participation at Madrasah Ibtidaiyah Assalam, Kajuara District, Bone Regency can be said to be good, because the community appreciates the activities held at the madrasah. In addition, the community knows and understands its duties and responsibilities in the implementation of education and the community also conveys its criticism and suggestions, so that the madrasah can improve these shortcomings.